Analysis of Content Marketing and Social Media Advertising on Sales Growth at MK SKIN - Nur Wulan Anggrainii; Muhammad Hamzah (Civiliza Publishing, Indonesia., 2026)
Advances in information technology have driven a shift in marketing patterns from conventional methods to digital marketing. This study aims to analyze the implementation of content marketing strategies, social media advertising, as well as supporting and inhibiting factors in increasing sales growth at MK Skin. The study used a qualitative approach with a case study research type. The research informants consisted of the owner of MK Skin Agent in Probolinggo Regency as key informants and social media admins as supporting informants selected using purposive sampling techniques. Data collection was conducted through interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and technical triangulation. The results showed that the content marketing strategy was implemented through the presentation of valuable, relevant, consistent, and interesting content that was able to increase audience engagement. Meanwhile, social media advertising was implemented by expanding the reach of advertising, determining the right target audience, presenting attractive ads, adjusting the frequency of display, and building interactions with social media users. The implementation of both strategies contributed to sales growth as indicated by the increase in the number of customers, sales turnover, and market reach. Supporting factors included content quality, publication consistency, and social media utilization, while inhibiting factors included changes in social media algorithms and high business competition.